Pengaruh Financial Knowledge, Financial Attitude, dan Locus Of Control terhadap Financial Management Behaviour pada Mahasiswa S1 Manajemen Fakultas Ekonomika dan Bisnis UNESA - Rahardiansyah, Ega; Isbanah, Yuyun (Seminar Nasional Manajemen, 2024)
The results of the national survey on financial literacy and inclusion conducted by the Financial Services Authority show that 85.10% of the population uses financial products and services. However, only 49.68% of the population has adequate knowledge, skills, confidence, attitudes, and behaviors in using financial service products. This research aims to determine the influence of Financial Knowledge, Financial Attitude, and Locus of Control on Financial Management Behavior among undergraduate Management students at the Faculty of Economics and Business, Universitas Negeri Surabaya. This research selects financial knowledge, financial attitude, and locus of control as independent variables. The population used in this study consists of undergraduate Management students at Universitas Negeri Surabaya. The purposive sampling method resulted in 103 research samples, with the criteria being students in their 4th semester or above, considering they have already taken financial management courses. Data analysis was conducted using multiple linear regression analysis with IBM SPSS 23 software. The results show that financial knowledge, financial attitude, and locus of control have a significant influence on financial management behavior.